Kontribusi Kepemimpinan, Kepuasan Kerja, dan Lingkungan Kerja terhadap Pencapaian Kinerja Karyawan PT. Kirana Permata - Irna Febriana; Fitantina; Bora Alviolesa (MOTIVASI, 2026)
Purpose– This study aims to determine the influence of leadership, job satisfaction, and work environment on employee performance at PT Kirana Permata Muara Enim. Design/methodology– The research design is associative. The independent variables in this study are leadership, job satisfaction, and work environment, while the dependent variable is employee performance. The population in this study was the permanent employees of the factory and office at PT Kirana Permata Muara Enim, totaling 282 people. A sample of 74 employees was selected using the 10% Slovin formula and cluster sampling. Primary data in this study were obtained from questionnaires, while secondary data were obtained from documentation. The data analysis techniques used were multiple linear regression, hypothesis testing (F-test and t-test), and the coefficient of determination. Findings - The results of the F test (simultaneous) indicate a significant influence of leadership, job satisfaction, and work environment on employee performance at PT. Kirana Permata Muara Enim. The results of the t-test (partial) prove that there is a significant influence of leadership on employee performance, there is an influence of job satisfaction on employee performance, and there is an influence of work environment on employee performance at PT. Kirana Permata Muara Enim. The coefficient of determination shows that leadership, job satisfaction, and work environment are able to contribute to increasing employee performance by 60.2%.